Employing a ROPMIS modeling to assess the effectiveness of railway stations in Indonesia - Hapsari, Yusita Titi; Setiarini, Diah Yuli; Irawan, Bambang; Soetriono (The Economics and Finance Letters, 2025)
This study employs ROPMIS modeling to evaluate the effectiveness of railway stations in Indonesia. In Indonesia, railways serve as a primary mode of transportation, and improving customer satisfaction can encourage the community to utilize public transportation as a means of addressing traffic congestion. However, research studies on the determinants of Indonesian railway performance using ROPMIS (resource, outcome, process, management, image, and social responsibility) are limited. Therefore, this present study aims to explore the determinants of customer satisfaction with railway stations in Indonesia using ROPMIS modeling. The data were obtained through questionnaires directed to railway customers and further analyzed using structural equation modeling. The finding of this study confirms that the ROPMIS modeling, including resource, outcome, process, management, image, and social responsibility, has a significant effect on customer satisfaction. The findings can be used to enhance the overall performance of railways in Indonesia. This study offers a novel model of relating how passenger satisfaction can promote railway performance in Indonesia. The findings of this investigation make a robust contribution to raising scholarly discourse on satisfaction and organizational performance. From a practical perspective, the paper can serve as a valuable guide for organizations such as PT. KAI Persero, helping them to enhance customer satisfaction and optimize train station performance in Indonesia.